Elucidating the mitochondrial function of murine lymphocyte subsets and the heterogeneity of the mitophagy pathway inherited from hematopoietic stem cells - Liang, Haoyue; Fu, Weichao; Yu, Wenying; Cao, Zhijie; Liu, Ertao; Sun, Fanfan; Kong, Xiaodong; Gao, Yingdai; Zhou, Yuan (Frontiers in Immunology, 2022)
Background: Mitochondria are mainly involved in ATP production to meet the energy demands of cells. Researchers are increasingly recognizing the important role of mitochondria in the differentiation and activation of hematopoietic cells, but research on how mitochondrial metabolism influence different subsets of lymphocyte are yet to be carried out. In this work, the mitochondrial functions of lymphocytes were compared at different differentiation and activation stages and included CD8+ T lymphocytes, CD4+ T lymphocytes, B lymphocytes, NK cells as well as their subsets. For this purpose, a complete set of methods was used to comprehensively analyze mitophagy levels, mitochondrial reactive oxygen species (ROS), mitochondrial membrane potential (MMP) and the mitochondrial mass (MM) of subsets of lymphocytes. Results and Discussion: Of all lymphocytes, B cells had a relatively high mitochondrial metabolic activity which was evident from the higher levels of mitophagy, ROS, MMP and MM, and this reflected the highly heterogeneous nature of the mitochondrial metabolism in lymphocytes. Among the B cell subsets, pro-B cells had relatively higher levels of MM and MMP, while the mitochondrial metabolism level of mature B cells was relatively low. Similarly, among the subsets of CD4+ T cell, a relatively higher level of mitochondrial metabolism was noted for naive CD4+ T cells. Finally, from the CD8+ T cell subsets, central memory CD8+ T cells had relatively high levels of MM and MMP but relatively low ones for mitophagy, with effector T cells displaying the opposite characteristics. Meanwhile, the autophagy-related genes of lymphoid hematopoietic cells were analyzed. The results showed that compared with CD4+ T, CD8+ T and NK cells, B cells were more similar to long-term hematopoietic stem cell (LT-HSC) and short-term hematopoietic stem cell (ST-HSC) in terms of their participation in the Pink1/Park2 pathway, as well as the degree to which the characteristics of autophagy pathway were inherited from HSC. Conclusion: This study is expected to provide a complete set of methods and basic reference values for future studies on the mitochondrial functions of lymphocyte subsets, and also provides a standard and reference for the study of infection and immunity based on mitochondrial metabolism.